Veneno de Latrodectus mactans de Chile (Araneae, Theridiidae): su efecto sobre músculo liso - Romero M, Fernando (2003)
The venoms of Latrodectus sp. have been reported to induce contraction probably mediated by adrenergic and cholinergic transmitters. We have demonstrated that the venom of Chilean Latrodectus mactans contains neurotoxins that induce a contraction partially independent of transmitters release. Transmembrane mobility of Na+ and Ca2+ ions and more specifically, the increase of cytoplasmic calcium concentration are responsible for tonic contraction in smooth muscle. Calcium may enter the cell by several ways, such as the voltagedependent Ca2+ L-type channels and the Na+/Ca2+ exchanger. This study aimed to examine the participation of this exchanger in the tonic contraction of smooth muscle in vas deferent of rat induced by the venom of the Chilean spider L. mactans. Blockers of Na+ channels (amiloride) and Ca2+ L-type channels (nifedipine), and a stimulator of the exchanger (modified Tyrode, Na+ 80 mM) were used. Simultaneously, variations of the cytoplasmic concentration of Ca2+ were registered by microfluorimetry (Fura-2 indicator) in the presence of nifedipine. In presence of amiloride, dose-dependent inhibition of venom-induced contraction was observed, suggesting the participation of voltage-dependent Ca2+ L-type channels. The contraction was only partially inhibited by nifedipine and the Ca2+ cytoplasmic concentration increased, as assessed by the microfluorimetric registration. Finally, the venom-induced contraction increased in the presence of modified Tyrode, probably due to the action of the Na+/Ca2+ exchanger. Taken together, our results support the idea that the Na+/Ca2+ exchanger is active and may be, at least in part, responsible for the contraction induced by the venom of Chilean L. mactans